2013
DOI: 10.1177/0015732513496619
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Subsidies and Environmental Sustainability: What does the Cross-country Empirical Estimates Suggest?

Abstract: A number of developed as well as developing countries provide subsidies to domestic players, leading to overproduction and over-exploitation of natural resources, which pose a serious threat to environmental sustainability. The analysis in this article attempts to understand the role of government budgetary subsidies on the overall environmental performance index through panel data model estimation for a set of 74 countries over an 11-year period (2000–2010). The empirical findings confirm the theoretical pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…Interestingly, this result contradicts the general belief that the private sector[6] emits more; and as emissions are a classic case of negative externalities, it would be overproduced in freer markets. Importantly, although these ndings are contrary to theoretical literature, what may be leading to unexpected outcomes, could possibly be the ine ciencies associated with production of both goods and services by the larger public sector [7]. Similar ndings are also reported in studies by Leblois However, population density is found to be positive and signi cant for all other regions, such as the Caribbean (Model 5), Latin America (Model 9), Mid East and North Africa (Model 4), the Paci c (Model 6) and Sub-Saharan Africa (Model 3).…”
Section: Econometric Analysis: Regional Classi Cations and Overall Po...contrasting
confidence: 94%
“…Interestingly, this result contradicts the general belief that the private sector[6] emits more; and as emissions are a classic case of negative externalities, it would be overproduced in freer markets. Importantly, although these ndings are contrary to theoretical literature, what may be leading to unexpected outcomes, could possibly be the ine ciencies associated with production of both goods and services by the larger public sector [7]. Similar ndings are also reported in studies by Leblois However, population density is found to be positive and signi cant for all other regions, such as the Caribbean (Model 5), Latin America (Model 9), Mid East and North Africa (Model 4), the Paci c (Model 6) and Sub-Saharan Africa (Model 3).…”
Section: Econometric Analysis: Regional Classi Cations and Overall Po...contrasting
confidence: 94%